Impact response of additively manufactured metallic hybrid lattice materials. (June 2017) - Harris, J.A.; Winter, R.E.; McShane, G.J.
Highlights: Metallic hybrid cellular structures were manufactured with selective laser melting. The hybrid geometry was created by combining honeycomb and lattice architectures. These structures were tested in quasi-static and dynamic compression up to 150 m/s. Performance was evaluated by seeking high energy absorption and low maximum stress. The hybrid geometry outperformed the benchmark square honeycomb at 100 m/s. Abstract: Additive manufacturing (AM) enables the design of new cellular materials for blast and impact mitigation by allowing novel material-geometry combinations to be realised and examined at a laboratory scale. However, design of these materials requires an understanding of the relationship between the AM process and material properties at different length scales: from the microstructure to geometric feature rendition to overall dynamic performance. To date, there remain significant uncertainties about both the potential benefits and pitfalls of using AM to design and optimise cellular materials for dynamic energy absorbing applications. This experimental investigation focuses on the out-of-plane compression of stainless steel cellular materials fabricated using selective laser melting (SLM), and makes two specific contributions. First, we demonstrate how the AM process itself influences the characteristics of these cellular materials across a range of length scales, and, crucially, how this influences the dynamic deformation. Secondly, we demonstrate how an AM route can be used to add geometric complexity to the cell structure, creating a versatile basis for future geometry optimisation. Starting with an AM square honeycomb (the reference case), we add porosity to the walls by replacing them with a lattice truss, while maintaining the same relative density. This geometry hybridisation is an approach uniquely suited to this manufacturing route. It is found that the hybrid lattice-walled honeycomb geometry significantly outperforms previously reported AM lattices in terms of specific strength, specific energy absorption, and energy absorption efficiency. It is also found that the hybrid geometry outperforms the benchmark metallic square honeycomb in terms of energy absorption efficiency in the intermediate impact velocity regime (i.e. between quasi-static loading and loading rates at which wave propagation effects begin to become pronounced), a regime in which the collapse is dominated by dynamic buckling effects.